The comparison of output constancy on linear accelerator between myQA Daily and Machine Performance Check - Arphasetthasakul , Wisan; Chotmit , Yupawadee; Suthon , Nichapa; Kumkhwao , Jumnong; Arphasetthasakul, Nussara (The Thai Journal of Radiological Technology, 2022)
Background: The daily output measurement of the linear accelerator is essential in sophisticated radiation techniques. The myQA Daily and the Machine Performance Check (MPC) can be used to assure the daily quality assurance of the linear accelerators in daily output measurements. Objective: this study is to compare the efficiency of two quality assurance tools, myQA Daily and MPC, in measuring the daily output measurement linear accelerators. Methods: The data of daily output were obtained for three months with myQA Daily and MPC measurements from the Varian TrueBeam at 6 MV, 6 MV-FFF photon beams and 6 MeV electrons. Results: the mean difference of daily output by the myQA Daily and MPC was no more than 1.00% and the largest difference was 1.07% at 6 MV photon beams. The concordance correlation coefficient was 0.68, 0.80 and 0.66 for 6 MV, 6 MV FFF and 6 MeV respectively. The Pearson correlation was 0.93, 0.89 and 0.80 for 6 MV, 6 MV FFF and 6 MeV respectively. Conclusions: he results from myQA and MPC show well agreement and correlation. The percentage difference from the daily dose measurement is not more than 2%.